FACTORS OF SOCIO-ECONOMIC AND CULTURAL DEVELOPMENT OF THE KUSHAN KINGDOM - Sobirov Jamshidbek (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article will talk about the occupation of the ancient Greco-Bactrian state by the yuechzhis, as well as the founding of the Kushan Kingdom, and about the socio-economic and cultural life of the Kushan Kingdom.